We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
134
1
avatar+701 

 If f(x) = x3 + 4x and g(x) = -2x + 1, then f(g(3))= ?

A)-195

B)-145

C)-77

D)-5

E)39

 Oct 4, 2018
 #1
avatar+18118 
+2

g(3) = -2(3)+1 = -5    now substitute this in to the  f(x) function

 

f(-5) = -5^3 + 4(-5) = -125 - 20 = -145      "B"   

 Oct 4, 2018

35 Online Users

avatar
avatar
avatar
avatar